Peran Artificial Intelligence dalam Meningkatkan Pembelajaran Interaktif Bahasa Arab - Hadi, Mardi; Qohar, Hendri Abdul (Dinasti Research, 2024)
The Arabic language plays a significant role in religious education, diplomacy, and economics; however, its learning process faces complex challenges, such as difficulties in understanding grammar (nahwu) and morphology (sharaf). This research aims to analyze how Artificial Intelligence (AI) can address these challenges and enhance interactive Arabic language learning, particularly in terms of personalization and effectiveness. The research employs a descriptive qualitative method by reviewing literature, scientific journals, and previous research reports, as well as conducting in-depth interviews with teachers and students utilizing AI technology. Data were also collected through observations of AI-based applications, such as chatbots and learning platforms, to understand their implementation and effectiveness. Analysis was performed using content analysis methods, supplemented by data triangulation, to produce valid and comprehensive findings. The study reveals that the transformation brought by artificial intelligence (AI) technology has revolutionized Arabic language learning by accelerating, simplifying, and personalizing the learning process. Key challenges, such as morphological complexity and dialectal diversity, have driven the development of technologies like Natural Language Processing (NLP) and AI-based voice recognition. Through an interdisciplinary approach that is culturally sensitive, AI is expected to create a more adaptive and inclusive Arabic learning experience.